Reexploring Female Pathways to Incarceration: Assessing the Role of Mental Illness - King, Sarah E. (International journal of offender therapy and comparative criminology, 2024)
The pathways framework represents an emerging body of work that emphasizes gendered-based influences on crime and incarceration. To date, studies on female pathways often minimize or exclude the role of mental illness. The current study employs Life Course Theory and the use of Life History Calendar to examine the pathways of a sample of 15 female prison inmates diagnosed with serious and persistent mental health conditions. Findings indicate that mental illness carried criminogenic risk throughout the life course, with crucial transitions of risk leading these women toward long term incarceration. Self-reported pathways included repeated victimization, substance use, psychological trauma, delinquency, and/or crime. This study suggests that the pathway framework would benefit from the increased recognition of the role of mental illness on female criminality. Trauma-informed policy implications are provided and discussed.